Brazilian Angiostrongylus cantonensis haplotypes, ac8 and ac9, have two different biological and morphological profiles - MONTE, Tainá Carneiro de Castro (2015)
Angiostrongylus cantonensis is the etiologic agent of eosinophilic meningoencephalitis in humans. Cases have been recorded in many parts of the world, including Brazil. The aim of this study was to compare the differences in the biology and morphology of two different Brazilian haplotypes of A. : ac8 and ac9. A significantly larger number of L1 larvae eliminated in the faeces of rodents at the beginning of the patent period was observed for ac9 haplotype and compared to the total of L1 larvae eliminated, there was a significant difference between the two haplotypes. The ac9 haplotype showed a significant difference in the proportion of female and male specimens (0.6:1), but the same was not observed for ac8 (1.2:1). The morphometric analysis showed that male and female specimens isolated from ac8 haplotype were significantly larger with respect to body length, oesophagus length, spicule length (male) and distance from the anus to the rear end (female) compared to specimens from ac9. The morphological analysis by light microscopy showed little variation in the level of bifurcations at the lateral rays in the right lobe of the copulatory bursa between the two haplotypes. The biological, morphological and morphometric variations observed between the two haplotypes agree with the observed variation at the molecular level using the cytochrome oxidase subunit I marker and reinforce the possible influence of geographical isolation on the development of these haplotypes.